2019
DOI: 10.1016/j.proci.2018.06.168
|View full text |Cite
|
Sign up to set email alerts
|

A self-contained progress variable space solution method for thermochemical variables and flame speed in freely-propagating premixed flamelets

Abstract: Flamelet models for premixed combustion, which are based on equations formulated and solved in progress variable space, have been proposed in the past, but have not been adopted for chemistry reduction methods. This is due to one limitation of these models: they need a closure for both the magnitude and the shape of the gradient (or scalar dissipation rate) of the progress variable, which is essential for an accurate prediction of the flame displacement speed. So far, solution methods for the aforementioned mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…( 12)) [28] and no generic analytical closure exists. In our previous works [28,29], a separate equation for the progress variable gradient has been utilized and it is likely that this approach can be extended to complement the composition space equations presented here. This aspect should be explored in future work.…”
Section: Discussion Of Conceivable Closures Cross-terms and Differential Diffusionmentioning
confidence: 99%
See 4 more Smart Citations
“…( 12)) [28] and no generic analytical closure exists. In our previous works [28,29], a separate equation for the progress variable gradient has been utilized and it is likely that this approach can be extended to complement the composition space equations presented here. This aspect should be explored in future work.…”
Section: Discussion Of Conceivable Closures Cross-terms and Differential Diffusionmentioning
confidence: 99%
“…A worthwhile extension of the present composition space theory is the consistent represen-tation of differential diffusion (non-unity Lewis numbers). Previous works on one-dimensional composition space modeling for premixed [28,29,34] and non-premixed combustion [39,40] have shown that this can be realized conditioning on either mixture fraction or progress variable. The extension of the two-dimensional composition space equations for differential diffusion requires a careful incorporation of detailed diffusion modeling leading to additional terms and transport effects, such as curvature-induced differential diffusion [41].…”
Section: Discussion Of Conceivable Closures Cross-terms and Differential Diffusionmentioning
confidence: 99%
See 3 more Smart Citations